Challenges and Barriers for Renewable Energy Implementation in the United Arab Emirates: Empirical Study - Al Shehhi, Aamna; Al Hazza, Muataz; Alnahhal, Mohammed; Sakhrieh, Ahmad; Al Zarooni, Mohamed (International Journal of Energy Economics and Policy, 2020)
One of the leader's countries with high awareness of Renewable Energy (RE) implementation is the United Arab Emirates (UAE). This research aims to statically investigate the challenges and requirements in the implementation of renewable energy in the UAE. A comprehensive literature review followed by a structured questionnaire was conducted. Eight different factors determined, and then a structured questionnaire was designed and distributed to 94 respondents. The results were analyzed using various statistical methods: one-sample t-test, unpaired two-sample t-test, two-proportion z-test, fisher test, and one-way ANOVA test. 0.98 and 1.000 value of one-sample t-test showed adequate infrastructure and technical skills. The two-sample t-test showed the main difference is in financing renewable energy and infrastructure between professionals and regular community. z-test showed consistent with a two-sample t-test. Fisher test presented positively rate governmental efforts except for the framework for land securement. ANOVA test displayed that the respondents' positions did not affect the perceptions about the availability of the requirements, except for technical skills, where people working on renewable energy projects are more optimistic regarding technical skills. In conclusion, a detailed study needs to be followed in our continuing efforts to analyze the readiness of the UAE to achieve its goals sat for 2050. Keywords: renewable energy, challenges, requirements, barriers, policies, UAE JEL Classifications: C120, Q4 DOI: https://doi.org/10.32479/ijeep.10585